2020
DOI: 10.1051/0004-6361/202038593
|View full text |Cite
|
Sign up to set email alerts
|

3D chemical structure of diffuse turbulent ISM

Abstract: Context. The amount of data collected by spectrometers from radio to ultraviolet (UV) wavelengths opens a new era where the statistical and chemical information contained in the observations can be used concomitantly to investigate the thermodynamical state and the evolution of the interstellar medium (ISM). Aims. In this paper, we study the statistical properties of the HI-to-H2 transition observed in absorption in the local diffuse and multiphase ISM. Our goal is to identify the physical processes that contr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 186 publications
(203 reference statements)
4
36
0
Order By: Relevance
“…Recent numerical simulations are able to follow the detailed evolution of H 2 directly and resolve the small-scale CNM (e.g., Nickerson, Teyssier, & Rosdahl 2019;Bellomi et al 2020). However, the CNM cross section depends heavily on resolution and on the poorly constrained feedback mechanisms from star formation and supernovae.…”
Section: Introductionmentioning
confidence: 99%
“…Recent numerical simulations are able to follow the detailed evolution of H 2 directly and resolve the small-scale CNM (e.g., Nickerson, Teyssier, & Rosdahl 2019;Bellomi et al 2020). However, the CNM cross section depends heavily on resolution and on the poorly constrained feedback mechanisms from star formation and supernovae.…”
Section: Introductionmentioning
confidence: 99%
“…In order to understand the effect of an energy-dependent spectral slope at a quantitative level, we first considered a slab with a fixed, spatially uniform B ⊥ exposed to a flux of CRe and we showed that, thanks to high-precision observational estimates of β at low frequencies (Mozdzen et al 2017), it is possible to discard some realisations of the CRe spectrum that would imply unrealistically high values of B ⊥ . Then, we used two snapshots of 3D MHD simulations (Bellomi et al 2020) with different median magnetic field strength, and studied the synchrotron emission according to the CRe spectrum by Orlando (2018). We computed the distribution of β for three frequency ranges, at low, mid, and high frequencies (115−189 MHz, 467−672 MHz, and 833−1200 MHz, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…To correctly describe the thermal state of the diffuse ISM, we have included the heating induced by the photoelectric effect on interstellar dust grains and secondary electrons produced during cosmic-ray propagation, and the cooling induced by emission of Lyman-α photons, the fine-structure lines of OI and CII, and the recombination of electrons onto grains. All these processes, described in Appendix B of Bellomi et al (2020), are modelled with the analytical formulae given by Wolfire et al (2003).…”
Section: Numerical Simulationsmentioning
confidence: 99%
“…Numerical studies show that the condensation process toward a stable CNM phase depends on the properties of turbulence in the WNM (Seifried et al 2011;Saury et al 2014;Bellomi et al 2020). These studies suggest that highly supersonic turbulence that is driven by compressive modes regulates the formation of a stable CNM phase as turbulent compression and decompression of the gas will be much more rapid than the cooling timescale.…”
Section: Mach Number Distributionmentioning
confidence: 95%